Foreign Bodies: the Body as Medium and the Body as Image in Contemporary Photography. Three Examples: John Coplans, Mona Hatoum ed Erwin Wurm - Michele Bertolini (piano b, 2022)
Contemporary Photograph investigates the human body in a fragmentary, partial dimension, quite different from the representation of the body’s organic unity. The essay aims to show the transformations of the body through the photographic representation: the body fragmented, the details of the body reveal the otherness and the strangeness inside the identity of the Self. The analysis of three works (John Coplans Self-Portaits, Mona Hatoum’s Van Gogh’s Back and Erwin Wurm’s One Minute Sculptures) points out the double condition of the body’s representation and the double status of photograph: the body as image and the body as medium, the photograph as performance and the photograph as image.